budget family food : Delicious money-saving meals for all the family - Wilson, Rebecca (London : Dorling Kindersley Limited, 2024)
From the bestselling author of What Mummy Makes Rebecca Wilson shows you how to bring comfort to your table with 80 recipes for nourishing, low-cost meals perfect for all the family. From quick breakfast taquitos and curried potato pasties to satisfy the pickiest of palettes, to moreish mushroom lasagne and decadent chocolate gingerbread cake, choose from 80 recipes packed with exciting flavours that will appeal to everyone at the table from 6 months and over. Whether you want to make fresh, fruity breakfasts, light snacks and air fryer treats, hearty slow-cooked casseroles, or sumptuous desserts, Rebecca's easy-to-follow recipes are designed to save you time and money, making the most of your favourite seasonal ingredients and store-cupboard essentials. With recipes tailor-made for Air-fryers and slow cookers, cooking once for all the family has never been simpler. With useful tips on budgeting, batch cooking, freezing and storing, easy substitutions for lots of ingredients, and catering to fussy eaters, Rebecca takes the worry out of meal planning and prep, so you can spend more quality time with the ones you love.
Includes index
Keywords: Low budget cooking